2021
DOI: 10.1186/s12913-021-07153-1
|View full text |Cite
|
Sign up to set email alerts
|

Is bouldering-psychotherapy a cost-effective way to treat depression when compared to group cognitive behavioral therapy – results from a randomized controlled trial

Abstract: Background Bouldering-Psychotherapy (BPT) has proven to effectively reduce depressive symptoms, but evidence on its cost-effectiveness is lacking. Corresponding information is paramount to support health policy decision making on a potential implementation of BPT in routine care. Methods Using data from the German KuS trial BPT was compared with group Cognitive Behavioral Therapy (CBT). Severity of depression symptoms at end of the intervention was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Reneman et al 23 found that the proportion caused by this disease accounted for 85% of the total cost. Schwarzkopf et al 24 found that, in the scenario of depression, the proportion of productivity loss in the total cost could be as high as 81%. Two studies found that productivity loss caused by rheumatoid arthritis accounted for 76% and 54% of the total costs, respectively 25 26.…”
Section: Resultsmentioning
confidence: 99%
“…Reneman et al 23 found that the proportion caused by this disease accounted for 85% of the total cost. Schwarzkopf et al 24 found that, in the scenario of depression, the proportion of productivity loss in the total cost could be as high as 81%. Two studies found that productivity loss caused by rheumatoid arthritis accounted for 76% and 54% of the total costs, respectively 25 26.…”
Section: Resultsmentioning
confidence: 99%
“…BPT (and probably CBT) seem suitable for a wide range of participants and could be chosen in a second step. Although being altogether at least as effective as only CBT and cost‐effective (Schwarzkopf et al, 2021), outpatient group BPT could be a good strategy.…”
Section: Discussionmentioning
confidence: 99%
“…These two intervention groups were compared with a home‐based exercise programme (EP). BPT was found to be superior to the EP (Karg et al, 2020) and CBT (Luttenberger et al, 2021) and was cost‐efficient (Schwarzkopf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TC is a promising method for treating depression. If someone has a systematic plan to practice it for a long time, their disease condition will improve [ 45 , 46 , 47 ]. The patient will feel better and can greatly enhance their social skills, self-management skills and self-efficacy.…”
Section: The Effects Of Tcmentioning
confidence: 99%